Por una causa justa - Grossman, Vasiliĭ (Galaxia Gutenberg, 2014)
The novel is set during the Second World War and focuses primarily on the first years of the war in Stalingrad. The plot mainly centres around the Shaposhnikov family and their close friends and relatives; however, it also extends to depictions of Hitler as well as a kolkhoznik.